Assessing the coverage of biofortified foods: Development and testing of methods and indicators in Musanze, Rwanda - Petry, Nicolai; Wirth, James; Friesen, Valerie; Rohner, Fabian; Nkundineza, Arcade; Boy, Erick; Birol, Ekin; Mudyahoto, Bho (American Society for Nutrition, 2020)
Biofortification is a promising approach to increase micronutrient intakes, especially among populations that are hard to reach with other interventions. Information on the coverage of biofortified foods is needed to ascertain potential for impact, understand program performance, and identify bottlenecks. In this study, we aimed to develop and test methods and indicators for assessing household coverage of biofortified foods.